Computational Fluid Dynamics Study Of Wake Recovery For Flow Across Hydrokinetic Turbine At Different Depth Of Water - Mohd Saat, Fatimah Al Zahrah; Hew, Wei Ren; Shikh Anuar, Fadhilah; Mat Tokit, Ernie; Abdul Wahap, Mohd Arizam; Tee, Boon Tuan (Penerbit Akademia Baru, 2021)
Depletion of fossil fuel caused mankind to look for sustainable and green energy resources. The characteristic of hydrokinetic turbine with ability to operate at low head stream and at low cost made it a good choice for use to harness hydro source of energy. As hydrokinetic turbine gain attention from the industry player, many experimental and Computational Fluid Dynamics (CFD) studies related to hydrokinetic turbine have been carried out. Yet the relationship of flow depth variation and wake recovery behind the turbine is still not fully understood. There is limited study about the effects of flow depth variations on the wake recovery behind the turbine. In this paper, a CFD model investigation was done based on published experimental work. A hydrokinetic water turbine was drawn using the MHKF1-180 and NACA4418 foils dimensions. The transient CFD study was conducted using SST k- turbulence model and dynamic mesh method. The results showed that in near wake region, the wake at deeper depth will recover faster seemingly due to pressure change at that depth and the faster rate of momentum transfer of the fluid. It can be concluded that the deeper the placement of the turbine inside the water channel, the faster the wake recovers. The wake recovery results as presented in this paper should be considered when placing set of turbines especially in array arrangement to obtain a more efficient energy conversion.